Biofilm Formation in Imipenem-Resistant Acinetobacter baumannii from the Intensive Care Unit - Mohammed F. Al- Marjani (Journal of Global Pharma Technology, 2017)
Acinetobacter baumannii is emerging as an important hospital pathogen, which can persist in the environment for extended periods of time. It is known to produce biofilms, a community of bacteria enclosed within a protective polymeric matrix. One hundred A. baumannii isolates were collected from patients from the intensive care unit (ICU). Antimicrobial susceptibility test was performed by disk diffusion method and MICs of imipenem were determined. Biofilm formation was assayed by micro titer plate and then PCR was performed for detection of ompA and bap genes. The results show that the imipenem-resistance was seen in 80% of A. baumannii isolates, and all these isolates were inferred to be (MBLs) producers. Among these isolates, 91.25% formed biofilms, 32.5% of isolates were categorized as moderately biofilm-producing isolates, 11.25% formed strong biofilms, and 8.75% of the isolates were non-biofilm producers. All isolates simultaneously carried the ompA gnes, whereas 70% of isolates harbored bap gene. Our results revealed a high prevalence of Metallo Beta-Lactamase and biofilm formation in Imipenem -resistant A. baumannii isolates from ICU.Keywords: Acinetobacter  baumannii, Imipenem -resistance, Biofilm, Iraq.